Pengaruh Terapi Aktifitas Kelompok Stimulasi Sensori Terhadap Psikososial Lanjut Usia Di Panti Werdha Himo-Himo Kota Ternate Tahun 2019 - arini krisnawati (Jurnal Kesehatan, 2020)
The state of deterioration in the condition of the elderly can cause balance disorders that lead to the elderly towards a progressive deterioration, especially psychological aspects. Group activity therapy is a therapeutic modality performed by nurses on a group of clients who have the same nursing problems, activities are used as therapy and groups  are used as targets of care. In the group there is a dynamic interaction that is interdependent, mutually needing and becomes a laboratory where clients practice new adaptive behaviors to improve old maladactive behaviors. The research method used quantitative with a quasi-experimental design using a pre-post test control group. The sample used by purposive sampling amounted to 40 people. Collecting data using observation techniques and guided interviews. The psychosocial observation sheet for the elderly is developed into 18 observations and each observation requires an alternative answer option. Data analysis using the Wilcoxon test. The results of the data test obtained a p-value of 0.000, then H1 was accepted and H0 was rejected because the p value was less than 0.05, meaning that there was an effect of Sensory Stimulation Group Activity Therapy on the Psychosocial Elderly at the Himo-Himo Home for the Elderly in Ternate City in 2019. Sensory stimulation group activity should be adapted to the ability of the elderly and must be liked by the elderly and in accordance  with the conditions